Exaggerated postprandial GLP-1 secretion following esophagectomy is not associated with gastric emptying and intestinal transit - Murphy, C F; Elliott, J A; Docherty, N G; Mohamed, A A; Vincent, R P; Ravi, N; Reynolds, J V; le Roux, C W (Diseases of the esophagus, 2021)
Summary Esophagectomy causes postprandial symptoms associated with an exaggerated postprandial gut hormone response. This study aimed to compare the gastrointestinal transit time of patients 1 year after esophagectomy with unoperated controls, including its relation to satiety gut hormone release. In this cross-sectional study, consecutive, disease-free patients after esophagectomy with pyloroplasty were compared with unoperated control subjects to assess gastric emptying (GE) and cecal arrival time (CAT). Serial plasma samples were collected before, and for 300 minutes after, a mixed-meal challenge. Body composition was assessed, and symptom scores were calculated. Eleven patients 1 year post-esophagectomy (age: 62.6 ± 9.8, male: 82%) did not show a significantly different GE pattern compared with 10 control subjects (P = 0.245). Rather, patients could be categorized bimodally as exhibiting either rapid or slow GE relative to controls. Those with rapid GE trended toward a higher postprandial symptom burden (P = 0.084) without higher postprandial glucagon-like peptide-1 (GLP-1) secretion (P = 0.931). CAT was significantly shorter after esophagectomy (P = 0.043) but was not significantly associated with GE, GLP-1 secretion, or symptom burden. Neither early nutrient delivery to the proximal small intestine nor to the colon explains the exaggerated postprandial GLP-1 response after esophagectomy. GE varies significantly in these patients despite consistent pyloric management.